2012
DOI: 10.1109/tmag.2012.2195721
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modelling of Magnetic Hysteresis in Exchange-Bias Spin Valves

Abstract: In this work we present a physical-related model of vector hysteresis for magnetic simulation of nanometric structures. The mathematical formulation, based on a generalization of the Preisach and Stoner-Wohlfarth models, is very simple and elegant. The numerical implementation is very easy and the computation time required for the simulations is extremely fast. However the accuracy is not comparable with the codes based on the micromagnetic theory, but it is sufficient for the use as preprocessing of more accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Each individual stage follows the general expression given by the VVPM [Eq. (4)], and we ensure continuity of σ B for −1 < m < 1. σ B is then given by (9) for the up cycle, and A phenomenological approach was used to identify each value of the exponent k, similar to recent works treating the modeling of the hysteresis of magnetic materials [28,31,65,66]. More precisely, they were obtained by fitting the measured [CoFeB(3Å)/Pd(10Å)] 15 multilayer, and application of the model to the remaining samples revealed that they remain unchanged as long as there is a negligible in-plane component of the magnetization.…”
Section: Distribution Of Interactionsmentioning
confidence: 99%
“…Each individual stage follows the general expression given by the VVPM [Eq. (4)], and we ensure continuity of σ B for −1 < m < 1. σ B is then given by (9) for the up cycle, and A phenomenological approach was used to identify each value of the exponent k, similar to recent works treating the modeling of the hysteresis of magnetic materials [28,31,65,66]. More precisely, they were obtained by fitting the measured [CoFeB(3Å)/Pd(10Å)] 15 multilayer, and application of the model to the remaining samples revealed that they remain unchanged as long as there is a negligible in-plane component of the magnetization.…”
Section: Distribution Of Interactionsmentioning
confidence: 99%
“…Hysteresis is a quite important magnetic property of Fe-3% Si grain-oriented electrical steel, since its hysteresis loops and magnetization curves reflect the significant characteristics of the material, which is also an important basis for the selection of cigarette machine sensor materials [11,12]. Study on the material hysteresis loop model is helpful to better understand the hysteresis property of the material, which is significant to the design of materials and related components [13]. With the increasingly higher demand of equipment design accuracy in the actual operation, it is necessary to accurately determine the impact caused by hysteresis [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental tests presented in this paper deal with static magnetization processes, which are useful to identify vector phenomenological models used for the prediction of hysteresis loops and hysteresis losses in bulk materials [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%